Pulmonary infection and baseline mRS scores predict poor prognosis in anti-GABABR encephalitis - Ding, Junqing; Xu, Dingkang; Lv, Jie; Wu, Tianwen; Li, Jinghong; Tian, Mi; Lian, Yajun (Frontiers in Immunology, 2022)
Purpose Anti-gamma-aminobutyric-acid type B receptor (anti-GABABR) encephalitis is a rare autoimmune condition caused by the presence of GABABR antibodies in the limbic system. However, its clinical features and prognostic factors are poorly understood. In this study, we aimed to explore factors that affect the response to first-line treatment in patients with anti-GABABR encephalitis. Methods Thirty-four patients with an initial diagnosis of anti-GABABR encephalitis were retrospectively enrolled from December 2015 to June 2021. Clinical features and experimental data recorded within 24 h of admission were extracted from the patients’ medical records. The modified Rankin Scale (mRS) was utilized to assess disease severity at admission and functional recovery after immunotherapy. Independent prognostic factors were determined by ordinal logistic regression analysis. Results Of the 34 anti-GABABR encephalitis patients, 12 (35%) presented with cancer; all of these patients had lung cancer. According to multivariate regression analysis, the cancer group exhibited a decrease in the peripheral blood absolute lymphocyte count (ALC) (odds ratio [OR]: 0.063, 95% confidence interval [CI]: 0.006-0.639, P=0.019) and hyponatremia (OR: 9.268, 95% CI: 1.054-81.502, 0.045). In addition, the neutrophil/lymphocyte ratio (NLR), monocyte/lymphocyte ratio (MLR) and platelet/lymphocyte ratio (PLR) did not significantly differ according to mRS scores in patients receiving first-line treatment. No patients with mild or moderate mRS scores (0-2) at admission developed symptoms after treatment; in contrast, only 11 patients with a severe mRS scores (≥3, 11/18) experienced symptom alleviation. Ordinal regression analysis indicated that worse prognosis was associated with pulmonary infection (OR=9.885, 95% CI: 1.106-88.323, P=0.040) and baseline mRS scores (OR= 24.047, 95% CI: 3.294-175.739, P=0.002) in the adjusted model. Conclusion Our findings demonstrate that pulmonary infection and baseline mRS scores are independent risk factors for poor prognosis in patients with anti-GABABR encephalitis after first-line treatment. ALC and hyponatremia are potential biomarkers for anti-GABABR encephalitis cases accompanied by lung cancer.